THE ROLE OF BRAND COMMUNITY COMMITMENT IN CREATING LOYALTY - Mahardhika Pamula; Susila Ihwan (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The present study aimed to analyze factors that lead to brand loyalty in community setting. A survey was carried out on a sample of 162 Panther Mania members. The proposed model was evaluated by using structural equation modelling. The mediating effects of brand community commitment were tested using Baron and Kenny’s (1986) logic. The results indicate that self-congruity positively influnces affective commitment stronger than continuence commitment. In addition, Both Brand affective commitment and brand continuence commitmen play a full mediaing effect for relationships. Brand affective commitment and continuence commitment were found to play a full mediating role in the raltionship between self-congruity and repurchase intention. Despite the mediating effect was stronger continuence commitment than affective commitment First, the next future need to add sample from more hedonic car community. Second, it should be able to incorporates qualitative and quantitave study to get more aqurate results. Third, reaserchs should conceptualize it more specifically whether the community in next studies categorized on simple brand community, brand communities or brand subculture.